A Reader’s Companion to the Confucian Analects - Rosemont, H. author. aut Link
XII, 75 p.
Keywords: This companion is not intended as another interpretation of the ancient text, but rather as an aid for contemporary students to develop their own interpretive reading of it, in the hope of thereby aiding them in the search for meaning, purpose, and service in their own lives - as seventy-three generations of Chinese have done.